2018
DOI: 10.1007/s10456-018-9604-y
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent LXR/RXR pathway modulation characterizes capillary remodeling in inflammatory corneal neovascularization

Abstract: Inflammation in the normally immune-privileged cornea can initiate a pathologic angiogenic response causing vision-threatening corneal neovascularization. Inflammatory pathways, however, are numerous, complex and are activated in a time-dependent manner. Effective resolution of inflammation and associated angiogenesis in the cornea requires knowledge of these pathways and their time dependence, which has, to date, remained largely unexplored. Here, using a model of endogenous resolution of inflammation-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 82 publications
(92 reference statements)
0
29
0
1
Order By: Relevance
“…1). 16,[20][21][22][23][24][25][26] For experiments involving treatment, dexamethasone (1 mg/mL Opnol; Clean Chemical Sweden AB, Borlange, Sweden) was given topically to the re-sutured eye immediately after suture placement and after that three times daily for 3 days. The control group was not treated.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 16,[20][21][22][23][24][25][26] For experiments involving treatment, dexamethasone (1 mg/mL Opnol; Clean Chemical Sweden AB, Borlange, Sweden) was given topically to the re-sutured eye immediately after suture placement and after that three times daily for 3 days. The control group was not treated.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Experimental design followed to investigate repeat neovascularization in the cornea using the suture model of inflammatory-induced corneal neovascularization. 16,[20][21][22][23][24][25][26] furthest invading vessel tips in slit-lamp photographs of the cornea and by the limbal border.…”
Section: In Vivo Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Paper IV, endogenous inhibition of inflammation was studied during the physiologic wound healing response. The endogenous healing process is comparable to the stabilization phase obtained by removing the angiogenic stimulus, studied by our group in another doctoral thesis: the hypothesis being that an endogenous inflammatory as well as angiogenic switch could be activated and deactivated through specific pathways, and that coordinated delivery of anti-VEGF and anti-inflammatory therapy could transform active sprouts into mature, non-leaky and non-damaging functional capillaries 113,325 .…”
Section: Wound Healing and The Endogenous Modulation Of Inflammation mentioning
confidence: 80%
“…The results showed that 124 chemical components originating from ZJP acted directly with 12 potential protein targets, suggesting the advantages of multiple components in ZJP in regulating endogenous metabolic changes in the body, showing the advantages of ZJP in the clinical treatment of CAG. Twelve targets were strongly associated with in ammation, including MAPK1, PTGS2, PTGS1, RXRA, ADRA1B, RB1, ADRB1, E2F1, SCN5A, PKIAIGF2, and GABRA1 [34][35][36][37]. Therefore, to verify the accuracy of the network pharmacology predictions and to further elucidate the potential mechanism of ZJP, we further tested the expression of these genes in gastric tissues of CAG rats.…”
Section: Discussionmentioning
confidence: 99%